FAKTOR-FAKTOR YANG MENENTUKAN INTENSI TURNOVER KARYAWAN DALAM ORGANISASI - Ni Wayan Mujiati; Anak Agung Sagung Kartika Dewi (Forum Manajemen STIMI Handayani Denpasar, 2016)
The event that often occurs in a system and human resource managementin some companies is how employees behave themselves. One of the employee’sbehavior is turnover intention which refers and led to employees to leave their job.This presentation will explore the factors that determine the turnover intentionof employees in organization. From the search results obtained, the factors thatdetermine turnover intention is; according to Mobley (1986) factors that determineturnover intention of employees divided into two: organizational factors andindividual factors. According to Mathis and John H. Jackson (2009) there are severalcomponents that determine turnover intention and whether the employee surviveor leave an organization include: organizational components, employee relations,career opportunities, rewards, and design tasks and jobs.